Studies of the optical and EPR data and the defect structure for the trigonal Cr3+ center in LaMgAl11O19 crystal. (April 2017) - Yang, Li-Rong; Liu, Chang; Mei, Yang; Zheng, Wen-Chen
Abstract: The complete diagonalization (of energy matrix) method based on the two-spin-orbit-parameter model (which takes into account of the contributions from both the spin-orbit parameter of d n ions in the traditional crystal field theory and that of ligand ions via covalence effect) is adopted to calculate uniformly the optical and EPR data of the trigonal Cr 3+ center in LaMgAl11 O19 crystal. The calculated results demonstrate that the observed nine optical and EPR data (six optical bands and three spin-Hamiltonian parameters g //, g ⊥ and D ) can be explained reasonably, which proves the effectiveness and practicality of the method in the unified calculations of optical and EPR data for crystals doped with d 3 ions. The defect structure of Cr 3+ center in LaMgAl11 O19 crystal due to the size mismatch is also estimated. Highlights: Optical and EPR data of trigonal Cr 3+ centers in LaMgAl11 O19 are calculated. Diagonalization method based on two-spin-orbit-parameter model is used. C alculated results agree with the observed values. Local lattice relaxation of Cr 3+ centers in LaMgAl11 O19 crystals is estimated.